2017
DOI: 10.1007/s10006-017-0667-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences between osteoradionecrosis and medication-related osteonecrosis of the jaw

Abstract: Understanding the clinical and underlying pathological differences between ORN and MRONJ probably contributes to the selection of appropriate treatment for each patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
21
0
3
Order By: Relevance
“…Over the past two decades, radiation delivery has evolved from three‐dimensional conformal RT (3D‐CRT) to intensity‐modulated RT (IMRT) and volumetric modulated arc therapy (VMAT), which uses computed tomography‐based planning and radiation delivery aided by computerised optimisation of multiple beam intensities 38 . The use of IMRT and VMAT reduces RT‐related complications, improves the patient quality of life, increases the survival rate and oncological prognosis and reduces ORNJ risk 38‐41 . In Taiwan, conventional 2DRT and 3D‐CRT have rapidly been replaced by IMRT or VMAT since 2009 24,25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, radiation delivery has evolved from three‐dimensional conformal RT (3D‐CRT) to intensity‐modulated RT (IMRT) and volumetric modulated arc therapy (VMAT), which uses computed tomography‐based planning and radiation delivery aided by computerised optimisation of multiple beam intensities 38 . The use of IMRT and VMAT reduces RT‐related complications, improves the patient quality of life, increases the survival rate and oncological prognosis and reduces ORNJ risk 38‐41 . In Taiwan, conventional 2DRT and 3D‐CRT have rapidly been replaced by IMRT or VMAT since 2009 24,25 .…”
Section: Discussionmentioning
confidence: 99%
“…proves the patient quality of life, increases the survival rate and oncological prognosis and reduces ORNJ risk. [38][39][40][41] In Taiwan, conventional 2DRT and 3D-CRT have rapidly been replaced by IMRT or VMAT since 2009. 24,25 Therefore, when analysing the effect of the RT modality on ORNJ risk, 2009 was defined as the cut-off year.…”
Section: Rt Modalitiesmentioning
confidence: 99%
“…It is well recognized that ORNJ is more progressive than MRONJ with a higher rate of complications such as pathologic fractures and extra-oral stulae [34,35]. Periosteal blood supply is more affected in ORNJ than MRONJ, probably explaining the worse ORNJ treatment outcomes [36]. A recent study reported a complete mucosal healing rate of 81.7% (67 of 82) after uorescence-guided bone removal in MRONJ patients [20].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence available on various reconstruction techniques, including mandibular reconstruction plates, autogenous bone grafts, regional flaps, and free tissue transfers in patients with ORN of the jaw rather than with MRONJ. [23][24][25] These studies have concluded that it is essential to be aware of the potential failures of reconstruction plates, particularly in patients with ORN who have received irradiation and therefore would exhibit wound healing problems.…”
Section: Discussionmentioning
confidence: 99%